Lipopolysaccharide Induces The Production Of Diagnostic Monoclonal Antibody By Hybridoma Cells Against Congenital Adrenal Hyperplasia - Chua, Gek Kee; Nur Anis, Mohamad Ariff (School of Engineering, Taylor's University, 2017)
The purpose of this research is to screen and identify the potential inducers in maximizing the production of monoclonal antibody by hybridoma 192 cell line for Congenital Adrenal Hyperplasia diagnostic. There are nine inducers used in this research, namely lysozyme, aldolase, sodium butyrate, sodium phosphate, potassium phosphate, dimethyl sulfoxide, lipopolysaccharide, essential amino acids, and nonessential amino acids. Hybridoma 192 cell was cultured in 5% CO2 incubator at 37°C and ˃80% humidity in the medium with different concentrations of inducer agents. The inducers were added at the beginning of the culture and the samples were taken after 72 h of culture. The performance of these inducer agents was assessed based on the maximum monoclonal antibody titer achieved using Enzyme-linked Immunosorbent Assay. Lipopolysaccharide was found to increase the maximum monoclonal antibody titer when supplemented at 8 to 12 µg/mL. After optimization using one-factor central composite design at this range, the optimum point was determined to be 8 µg/mL. Verification experiments show that lipopolysaccharide enhanced the average specific monoclonal antibody production rate by 56% relative to control. In conclusion, lipopolysaccharide at 8 µg/mL is able to increase the monoclonal antibody specific production of hybridoma 192 cell line.